2017
DOI: 10.1002/prep.201700109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aluminum Particle Size on the Detonation Pressure of TNT/Al

Abstract: To better understand the influence of the aluminum particle size on the detonation pressure of TNT/Al, electrical conductivity experiment and detonation pressure experiment were performed in this study. Four types of TNT/Al were considered, in which the particle size of aluminum was 50 nm, 100 nm, 1.50 μm, and 9.79 μm, respectively. The combustion process of Al in TNT/Al was detected by electrical conductivity experiment, and the detonation pressures of TNT/Al were measured by using the manganin pressure senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Where the reaction rate constant M is the parameter related to the particle size of aluminum powder, a higher M is associated with a faster aluminum reaction rate, moreover, aluminum reaction rate is inversely proportional to particle size of aluminum powder [19], therefore, M is also inversely proportional to the particle size of aluminum powder. a, b are the reaction rate exponents.…”
Section: Time-dependent Jwl Equation Of Statementioning
confidence: 99%
“…Where the reaction rate constant M is the parameter related to the particle size of aluminum powder, a higher M is associated with a faster aluminum reaction rate, moreover, aluminum reaction rate is inversely proportional to particle size of aluminum powder [19], therefore, M is also inversely proportional to the particle size of aluminum powder. a, b are the reaction rate exponents.…”
Section: Time-dependent Jwl Equation Of Statementioning
confidence: 99%
“…Compared with traditional aluminum particles, aluminum nanoparticles (ANPs) have a higher chemical reactivity, and they can rapidly react in the high-temperature and high-pressure conditions of explosive detonation. The energy released can support propagation of the detonation wave, which can greatly improve the power of explosives, 1 and ANPs are being increasingly added to explosive components. [2][3][4][5] During shock initiation and detonation of aluminized explosives, the shock wave will interact with the aluminum particles, and with reflection and convergence of the shock wave, as well as transfer and transformation of energy, a complex hightemperature and high-pressure field will be generated.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [12] have studied the catalytic effect of nanometer aluminum powder and micrometer aluminum powder on nitro explosive RDX with TG‐DSC methods and found that nanometer Aluminum powder has an obvious catalytic effect. Zhou et al [13] have studied the effect of different sizes of nano‐aluminum on the detonation pressure of TNT/Al composite explosives. Queenie et al [14] have used Dynamic Stability Control (DSC), Thermo Gravimetric Analyzer (TG‐DTA), and ARC (accelerating rate calorimeter) simultaneously to study the thermal decomposition behavior of nano‐aluminum and micro‐aluminum.…”
Section: Introductionmentioning
confidence: 99%